Leveraging on Adult Literacy Education for Community Development in Nigeria - Murtala Akanbi Yusuf; Ibrahim Abdullahi Shehu (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
The purpose of this research is to look at leveraging on adult literacy education for community development in Nigeria. The research examines certain connected literatures on the subject at hand. Based on a thorough assessment of the literature, it was discovered that a person is literary when he has gained the necessary knowledge and abilities to engage in all the activities that require literacy for efficient functioning in his group or community. Furthermore, adults in communities require more than basic literacy knowledge; they also require functional literacy. Global attempts to eradicate poverty, ignorance, and illiteracy, among other things, as outlined in the Millennium Development Goals, would be ineffective unless appropriate initiatives based on the adult population, the pivot of dynamic and sustainable development, are implemented. Adult literacy education programmes are indeed critical tools for transforming Nigerian communities. Without the growth of human potential, the creation of high-rise buildings and other infrastructure in communities will not result in the essential change.